A level playing field : school finance in the Northeast - Morse, Jane Fowler, 1940- (State University of New York Press, 2007)
"In this work, Jane Fowler Morse reviews the history of school finance litigation in the United States and then examines recent legal and political struggles to obtain equitable school funding in New York, Vermont, and Ontario. These three places have employed strikingly different strategies to address this issue, and Morse analyzes lessons learned at each that will benefit both public officials and citizens interested in seeking reform elsewhere. Drawing on writers from Aristotle to Cass Sunstein and Martin Luther King Jr., she also explores the concepts of social justice and equity, highlighting the connections between racism, poverty, and school funding. The result is a passionate plea for equitable funding of public education nationwide to instantiate the ideal of "liberty and justice for all.""--Jacket